Manajemen Pengawasan Pendistribusian Zakat pada Baznas Kota Binjai - M. Ariiq Hawwari; Soiman (Fakultas Ushuluddin Adab dan Dakwah UIN Sultanah Nahrasiyah Lhokseumawe, 2026)
This study analyzes the supervision management of zakat distribution at the National Zakat Board (BAZNAS) of Binjai City. The research is motivated by the limited studies examining the integration of sharia supervision, mustahik verification, and information technology utilization in local-level zakat distribution management. A qualitative descriptive approach was employed, with data collected through interviews, observations, and document analysis. The findings indicate that BAZNAS Binjai implements supervision through sharia audits, Standard Operating Procedures (SOP), and the BAZNAS Management Information System (SIMBA). However, the effectiveness of supervision is constrained by limited human resources, inaccuracies in mustahik data, and inadequate technological infrastructure. To address these challenges, BAZNAS applies layered verification mechanisms, strengthens cross-sector collaboration, and enhances staff capacity. This study contributes to the literature on zakat governance by highlighting the importance of an integrated supervision system in improving transparency, accountability, and the accuracy of zakat distribution.